Marx, population and freedom - Julian Roche (The White Horse Press, 2020)
Marxists have long moved beyond a perception of Marx as a Promethean ecological vandal. Yet those disputing his environmental credentials are generally united in deploring the unhappy history of population control. They implicitly accept the idea of currently forecast future population levels as consistent with a Marxist view of human emancipation. This assumption should be challenged, on the basis of what resources a truly unalienated future may require in order to achieve real freedom for each future individual.